Penerapan ular tangga dalam meningkatkan pemahaman al-qur’an dan hadits di MIN Kota Blitar - Muchofifah, Azza Rukyatul (Maliki Interdisciplinary Journal, 2024)
This study explores the application of the traditional game Snakes and Ladders as an educational tool to enhance the understanding of the Qur’an and Hadith among students at MIN Blitar City. Utilizing a quasi-experimental design, the research involved a sample of students who participated in regular class activities and those who engaged with the educational version of Snakes and Ladders. The game was adapted to include questions and tasks related to key concepts from the Qur’an and Hadith, aiming to make learning more interactive and engaging. Pre- and post-tests were administered to measure the students’ comprehension levels. The results indicate a significant improvement in the understanding of religious texts among students who used the game, highlighting the effectiveness of gamified learning in religious education. This study suggests that incorporating educational games can be a valuable strategy in religious studies, providing a fun and motivating learning environment that enhances students’ engagement and comprehension.